The whole life prostate book : everything that every man-at every age-needs to know about maintaining optimal prostate health - Carter, H. Ballentine (Free Press, 2012)
"One of the world's preeminent prostate cancer doctors offers the authoritative and definitive guide for men of all ages for better prostate health and longevity. The book is sure to become for prostate health what Dr. Susan Love's Breast Book has been for breast health the book that everyone will want to read.For the 20 million men who are currently coping with prostate health issues in the U.S., and for the 200,000 diagnosed with prostate cancer every year, The Whole Life Prostate Book is the best go-to resource for everything patients and their families need to know to survive and thrive. And this book isn't only for those diagnosed with cancer; every man whether in his 20s, 30s, or over sixty is one day closer to prostate problems, unless he is ready to make positive changes in his health. Lifestyle choices diet, exercise, and health maintenance can defy prostate cancer; according to Dr. Carter, it's never too late, or too early, to start following his preventive program. Director of Adult Urology at the Johns Hopkins University School of Medicine and a world-renowned expert in the diagnosis and treatment of prostate disease, Dr. H. Ballentine Carter has packed this book with wisdom gleaned from his many years in the field. Cutting through the overwhelming amount of information and misinformation on the topic, Dr. Carter arms men with the knowledge required to make the best decisions about prevention, testing, and treatment. In easy-to-understand language, Dr. Carter explains how to read test results and outlines all of the treatment options available for prostate cancer, from radiation therapy and radical prostatectomy to brachytherapy and Proactive Surveillance, an innovative approach pioneered by Dr. Carter and designed to preserve the prostate for life. Fearlessly tackling the problem head-on, this guide will be a lifesaver for countless readers"--Provided by publisher.